Mechanisms of sulphur dioxide induced bronchoconstriction in normal and asthmatic man. Issue 2 (February 1982) - Snashall, P D; Baldwin, C
Abstract : We have examined the inhibitory effect of atropine and sodium cromoglycate (SCG) on the bronchial response to sulphur dioxide (SO2) in groups of normal and asthmatic subjects. Eleven normal subjects were premedicated with propranolol (100 mg orally) one hour before each experiment. After baseline measurements of specific airways conductance (sGaw) the subject inhaled an aerosol from a Wright nebuliser for five minutes. In separate experiments this contained water (control), atropine methonitrate (0 . 2%), or SCG (1%). Fifteen minutes later sGaw was remeasured and the subject then breathed SO2 (8 ppm) for three minutes through the mouth. Specific airways conductance was measured for the duration of the subsequent response. Intervals between experiments on any one subject were one week or more. After control SO2 inhalation sGaw decreased in all subjects (mean 34 +/- 17 (SD)%). Atropine and SCG significantly inhibited the SO2 response (p less than 0 . 01 for both). After atropine the mean decrease in sGaw was 13 +/- 24%; after SCG 16 +/- 12% (range -3- + 55%). With atropine the degree of inhibition was inversely related to the subject's responsiveness to the control SO2 inhalation (r = 0 . 75; p less than 0 . 01). In four asthmatics (without beta-blockade and with lower SO2 exposure) atropine did not inhibit the SO2 response; SCG had a similar effect to that seen in normal subjects. Therefore, vagal efferent mechanisms are involved in the bronchial response to SO2 in normal subjects, but the lack of inhibition caused by atropine in hyperreactive normal and asthmatic subjects suggests that vagal mechanisms are not important in the causation of hyperreactivity to SO2. The mechanism of inhibition with SCG is unknown.